IN SCIENTIFIC AND CULTURAL RELATIONS BETWEEN THE WEST AND THE EAST THE IMPORTANCE OF THE GREAT SILK ROAD (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the processes of socio-cultural and scientific integration between the Western and Eastern countries of the Great Silk Road. The East and the West represent the historical development of mankind and are the centers of civilization. On this land, people with their minds and selfless labor created civilizations that are inscribed in golden letters on the pages of history. From here came thinkers who made great discoveries in the field of science, engineering and technology. Their achievements today have become the property of all mankind and continue to serve it. These achievements are recognized in science as civilizational, due to their influence on the development of society at a new high level.